Nuansa Pendidikan Islam Dalam Undang-Undang RI No. 20 Tahun 2003 Tentang Sisdiknas: Peran dan Tujuan Pendidikan Nasional - Kasiono; Bahaking Rama; Muhammad Rusdi Rasyid (CV Putra Publisher, 2022)
The national education system which is based on Law no. 20 of 2003 concerning the national education system has provided a broad space for Islamic education in various forms and models of its implementation. For Muslims in Indonesia, this is certainly a very strategic matter related to the continuity of Islamic education as one of the main foundations for preserving and passing on the values ​​of Islamic teachings through the educational process. Islamic religious education is education that teaches good values ​​which are then implemented in life. Islamic education itself has an important role in the history of the development of the Indonesian nation, especially in terms of the historical dimension where Islamic education has been a formal education for centuries known as pesantren. The purpose of this study is to determine the relationship, the role of Islamic education in the national education system because to make a balanced human being from an intellectual point of view, religious education is needed, namely Islamic education in order to achieve national education goals. The method used in this study uses a qualitative research method with a type of library research (library research). Based on the results of the study it can be concluded that Islamic education in the national education system is that Islamic education occupies a position as a formal, non-formal, informal, and religious institution.